Anti-War Messages in the Songs of John Lennon - Dahal, Arvind (JODEM: Journal of Language and Literature, 2021)
This study endeavors to explore Lennon’s songs as an expression of rage and rebellion of the common Americans against the bitter realities of the contemporary American war politics of the 1960s and 70s and of the prevailing socio-economic and cultural injustices. It illumines a reality that alternative cultures like drugs, alcohol, homosexuality, nomadism and mystic vision, perceived reprehensible by the contemporary mainstream culture, were in fact manufactured out of harsh American socio-political context. By projecting the painful experiences of the victims during the time of war, the research engages with the extraction of themes like terror of the nuclear arms race and poverty, racism, prison and war, buried in Lennon’s compositions and thereby revealing Lennon’s association with such subcultures to counter and to subvert the mundane, the rationality and material hunger of the mainstream culture in the then America.